Essential role of the Cdk2 activator RingoA in meiotic telomere tethering to the nuclear envelope - Petra Mikolcevic; Michitaka Isoda; Hiroki Shibuya; Ivan del Barco Barrantes; Ana Igea; José A. Suja; Sue Shackleton; Yoshinori Watanabe; Angel R. Nebreda (Nature Communications, 2016)
CDKs play central roles in cell cycle regulation and are normally activated by cyclins. Here the authors show that RingoA induces a cyclin-independent function of CDK2 at meiotic telomeres, which regulates their tethering to the nuclear envelope and proper synapsis of homologous chromosomes.